2017
DOI: 10.1002/cbf.3278
|View full text |Cite
|
Sign up to set email alerts
|

Fractalkine/CX3CR1 induces apoptosis resistance and proliferation through the activation of the AKT/NF‐κB cascade in pancreatic cancer cells

Abstract: Fractalkine (FKN, CX3CL1) is highly expressed in a majority of malignant solid tumours. Fractalkine is the only known ligand for CX3CR1. In this study, we performed an analysis to determine the effects of fractalkine/CX3CR1 on modulating apoptosis and explored the related mechanisms. The expression of fractalkine/CX3CR1 was detected by immunohistochemistry and western blotting. The levels of AKT/p-AKT, BCL-xl, and BCL-2 were detected by western blotting. Then, the effects of exogenous and endogenous fractalkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…The apoptosis of MDA-MB-231 and HCC1937 cells treated with sh-NC, sh-PUF60, OE-NC, or OE-PUF60 was determined by flow cytometry assay with Annexin V (FITC)/propidium iodide (PI) apoptosis detection kit (KeyGEN Biotech, Jiangsu, China) according to previous study 19…”
Section: Methodsmentioning
confidence: 99%
“…The apoptosis of MDA-MB-231 and HCC1937 cells treated with sh-NC, sh-PUF60, OE-NC, or OE-PUF60 was determined by flow cytometry assay with Annexin V (FITC)/propidium iodide (PI) apoptosis detection kit (KeyGEN Biotech, Jiangsu, China) according to previous study 19…”
Section: Methodsmentioning
confidence: 99%
“…In another PNI tumor, CCA, studies showed that NF-κB signaling could be activated by the CCL5/CCR5 axis through increasing the expression of MMP2 and MMP9, thus contributing to the invasion and metastasis of tumor cells, which could be inhibited by CCL5 neutralizing antibody or CCR5 inhibitor maraviroc (94). Wang et al (95) found that CX3CL1/CX3CR1 could promote the invasion of pancreatic cancer through the activation of the NF-κB signaling pathway (Fig. 3).…”
Section: Reciprocal Interaction Between Other Factors and Chemokines mentioning
confidence: 98%
“…Importantly, chemokines can promote tumor cell survival by regulating the balance between NF-κB-associated pro-and antiapoptosis proteins. CCR5 and CX3CL1 were demonstrated to promote the expression of antiapoptotic and tumor-promoting proteins such as Bcl-xl, Bcl-2, and C-IAP1, as well as to reduce the expression of apoptotic proteins including cleaved caspase-3 and -9, PARP, and Bax via the NF-κB pathway [99,100].…”
Section: Roles Of Chemokines In Tumor Growth and Proliferationmentioning
confidence: 99%
“…Furthermore, in HCC patients, CX3CL1/CX3CR1 regulates the cancer cell cycle and tumor progression via the autocrine or paracrine systems, which is associated with positive outcomes [211]. In contrast, CX3CL1/CX3CR1 has been proven to induce tumor growth, proliferation, and apoptosis resistance through activating the AKT/NF-κB [100] and JAK/STAT signalling pathways in PDAC [212]. Therefore, a study in PDAC patients showed evidence that high expression of the CX3CL1/CX3CR1 axis in tumor tissues led to a poor prognosis for OS [213].…”
Section: Cx3cl1/cx3cr1mentioning
confidence: 99%